New cyclopentaquinoline and 3,5-dichlorobenzoic acid hybrids with neuroprotection against oxidative stress for the treatment of Alzheimer’s disease - Kamila Czarnecka; Małgorzata Girek; Paweł Kręcisz; Robert Skibiński; Kamil Łątka; Jakub Jończyk; Marek Bajda; Piotr Szymczyk; Grzegorz Galita; Jacek Kabziński; Ireneusz Majsterek; Alba Espargaró; et al. (Journal of Enzyme Inhibition and Medicinal Chemistry, 2023)
Alzheimer’s disease (AD) is a progressive neurodegenerative brain disease. Thus, drugs including donepezil, rivastigmine, and galantamine are not entirely effective in the treatment of this multifactorial disease. The present study evaluates eight derivatives (3a–3h) as candidates with stronger anti-AD potential but with less side effects. Reactive oxygen species (ROS) assays were used to assess oxidative stress which involve in the neurodegeneration. The neuroprotective properties of 3e against oxidative stress were done in three experiments using MTT test. The anti-AD potential was determined based on their anticholinesterase inhibition ability, determined using Ellman’s method, Aβ aggregation potential according to thioflavin (Th) fluorescence assay, and their antioxidative and anti-inflammatory activities. Compound 3e exhibited moderate cholinesterase inhibition activity (AChE, IC50 = 0.131 µM; BuChE, IC50 = 0.116 µM; SI = 1.13), significant inhibition of Aβ(1–42) aggregation (55.7%, at 5 µM) and acceptable neuroprotective activity. Extensive analysis of in vitro and in vivo assays indicates that new cyclopentaquinoline derivatives offer promise as candidates for new anti-AD drugs.